Pacto laboral e ganhos do atleta profissional de futebol. - Sá Filho, Fábio Menezes de (2009)
The employment contract of the professional football player has some peculiarities which are only found in that specific cathegory of athletes. To this effect, it shall be applied whenever feasible, the norms established by Brazilian Federal Law number 9.615, from 24 March 1998, well known as Normas Gerais sobre Desporto, or Pelé’s Law, and when not, the complementary rules of Consolidation of Labor Laws (CLT). Based on the directives estabilished in that same law, that all other regulations in that sporting modality are rooted. Throughout this monographic work, we shall delve into the characteristical particularities of this sport employment contract, focusing on the analysis of the juridical nature of the professional athlete's earnings and the juridical consequences originated from the extinction of the Free Pass System.